Factors affecting diesel fuel degradation using a bespoke high-pressure fuel system rig. (January 2018) - Gopalan, Kesavan; Smith, Christopher R; Pickering, Simon G; Chuck, Christopher J; Bannister, Christopher D
Recently, there has been automotive-industry-wide impetus to reduce the overall diesel vehicle emissions and the fuel consumption by increasing the fuel injection pressure within common-rail systems. Many production fuel injection systems are now capable of delivering rail pressures of 1800–2000 bar, with those able to achieve 3000 bar under development. In addition, there has been a gradual increase in the permitted fatty acid methyl ester content in EN 590 diesel from 5% to 7% with further increases to 10% proposed. With these changes, there has been mounting speculation that increasing the injection pressure, particularly with an elevated biodiesel content, can contribute to fuel degradation, deposit formation, fuel filter blocking and corresponding vehicle reliability issues. In this investigation, a bespoke high-pressure fuel injection rig was designed and commissioned to mimic conditions representative of those experienced within a modern vehicle engine. The impacts of the rail pressure, the biodiesel content and the accelerated testing conditions on the stability of the diesel fuel and deposit formation leading to filter blocking were assessed. Despite the abundance of literature on laboratory-based biodiesel degradation, in these more realistic operating conditions it was found that biodiesel did not increase the likelihood of deposit formation within the high-pressure fuel system, with the same level of filter blocking observed for both the baseline diesel B0 (i.e. no biodiesel) and the B10 blend (which contains 10% biodiesel). This implies that the filter-blocking problem caused by onboard fuel degradation has the potential to occur broadly in a wide range of different fuel compositions. B10 fuel tested with a rail pressure of 2000 bar resulted in a pressure drop across the fuel filter of 0.5 bar within 12, 000 min (approximately 8.3 days), whereas the corresponding experiment at a rail pressure of 1000 bar showed no increase in the filter pressure. When using model (B10) fuel, filter blocking was observed at rail pressures of both 2000 bar and 1000 bar, but with a lower pressure at a much reduced rate, leading to the belief that the increases in the rail pressure towards 2000 bar has a significant effect on the propensity of vehicle diesel filters to block. Measures taken to increase the severity of the test, such as recirculating injected fuel to simulate shear effects, were found to increase the rate of degradation but did not change the chemical composition of the solids formed, thus implying that they were valid methods of reducing the test duration without introducing new degradation mechanisms. The rig presented here is therefore a suitable accelerated testing system for assessing the behaviour of fuels at higher pressures that will be common throughout the global diesel fleet in the near future.